The Effect of Welding Speed on the Micromorphology and Mechanical Properties of Laser-Sealed Vacuum Flat Glazing Joints - Hong Miao; Chong Li; Qiang He; Shanwen Zhang; Yanjun Zhang; Sixing Liu (Advances in Materials Science and Engineering)
To explore the effect of welding speed on the micromorphology and mechanical properties of the laser-welded vacuum plate glazing joints, this paper introduced the research status of the laser welding vacuum glazing and then carried out the preparation for experimental materials. This paper also analyzed the microstructure, the cause of the pores, and the mechanical properties of the sealing layer. The results show that the smaller the welding speed is, the more fully the solder melts. When the welding speed is 80 mm/min, the sealing layer generates the large thermal stress due to excessive laser input energy, which results in many connected cracks in the sealing layer. The porosity of the sealing layer increases with the increase of the welding speed. The thickness of the interface reaction wetting layer decreases with the increase of the welding speed. The hardness, tensile strength, and shear strength of the sealing layer will increase first and then decrease with the increase of welding speed. These studies can provide the theoretical basis for laser sealing manufacturing of vacuum plate glazing.